EKSPRESI FANATISME ARMY PENGGEMAR BTS (PEREMPUAN) DI INDONESIA DALAM INSTAGRAM - Samudra Sindy Pertiwi; Triyono Lukmantoro; Amida Yusriana (Interaksi Online, 2023)
The phenomenon of fan culture is currently occurring in various aspects of humanity, both cultural, social, economic, political, and entertainment. The fan culture phenomenon was formed because of a set of norms originating from the fans themselves. However, fan culture is slowly experiencing changes in fandom activities. The Indonesian ARMY fandom is known as a loyal fan of BTS, it is not uncommon for them to show their fanatical behavior by often posting everything about BTS. This research aims to find out what ARMY's motivation is for following BTS, what activities occur, and what forms of fanaticism are expressed on Instagram. Several theories are used to examine this phenomenon, including the Bandwagon Effect Theory, Parasocial Relationship Theory, and Participatory Culture Theory. The method used is descriptive qualitative with a phenomenological approach that focuses on the experiences of the informants. To dig up in-depth information from informants, researchers used in-depth interview techniques (in dept interviews). The results of this research show that ARMY's motivation for following BTS can be explained as coming from the circle or joining the group and the interest comes from themselves. ARMY's motivation for liking BTS can also be explained by the way individuals like or love their idols because of the physical factors they display. The activities on social media can create a sense of intimacy, feelings of connection, friendship, and identification with media figures. Active activities that are usually carried out by informants can be shown by giving likes, replying to comments, and sending messages on Instagram as well as re-sharing uploads about BTS. Several activities carried out by the informant indirectly made the informant feel closer to ARMY, which was part of a social relationship. Expressions of fanaticism can be shown in various ways on Instagram, namely by watching concerts, creating short video content about BTS at concerts, uploading concert photos, creating merchandise unboxing content to immortalize, and collecting merchandise, starting from albums, photocards, clothes, hats, etc. and other trinkets, are part of the indicators of participatory culture, namely producing, reading and writing.